Reinventing the South versions of a literary region - Winchell, Mark Royden, 1948- (University of Missouri Press, 2006)
"Surveys the revivification and reinvention of southern culture and literature, and the influence of the Agrarians, Fugitives, New Critics, and popular writers, including John Gould Fletcher, Robert Penn Warren, Monroe K. Spears, Walter Sullivan, William Faulkner, Tennessee Williams, William Humphrey, and Cormac McCarthy"--Provided by publisher.